2019
DOI: 10.1002/ijgo.12842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cesarean delivery rates at three university hospital labor units using the Robson classification system

Abstract: Objective To analyze the frequency of cesarean delivery using the Robson 10‐group classification. Methods A multicenter retrospective cohort study was conducted at three university hospital labor units in the Slovak Republic. The medical records of all women who gave birth at these centers from January 1 to December 31, 2017, were assessed. Results In all, 1437 of 3361 (42.8%), 729 of 2795 (26.1%), and 303 of 2080 (14.6%) births recorded at the three centers during the current study period were by cesarean del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The HUSM presented results similar to the ones recorded by Tapia et al (2016) 17 in Latin America and by Yadav et al (2016) 18 in India when it started to perform all childbirths, not just the high-risk ones. 17 18 Therefore, the comparison between Robson Classification results and data available in the literature allowed observing that the frequency of pregnant women in each group was associated with population type, as it was also reported by Zahumensky et al (2019), 14 who compared three Slovak centers presenting different healthcare profiles: one tertiary center with neonatal intensive care unit (NICU), intensive care unit (ICU) and two other centers that only treated pregnant women with gestational age > 32 weeks. The aforementioned study has found differences in the most recurrent Robson groups in each service, as well as cesarean section rate variations from service to service.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…The HUSM presented results similar to the ones recorded by Tapia et al (2016) 17 in Latin America and by Yadav et al (2016) 18 in India when it started to perform all childbirths, not just the high-risk ones. 17 18 Therefore, the comparison between Robson Classification results and data available in the literature allowed observing that the frequency of pregnant women in each group was associated with population type, as it was also reported by Zahumensky et al (2019), 14 who compared three Slovak centers presenting different healthcare profiles: one tertiary center with neonatal intensive care unit (NICU), intensive care unit (ICU) and two other centers that only treated pregnant women with gestational age > 32 weeks. The aforementioned study has found differences in the most recurrent Robson groups in each service, as well as cesarean section rate variations from service to service.…”
Section: Discussionsupporting
confidence: 52%
“…This outcome highlighted the influence of healthcare profile on the delivery and cesarean rates in each service. 14 Based on results of the present study, most women belonged to group 5 during data collection at the HUSMthis group accounted for $ 25% of childbirths. This finding confirms the fact that the incidence of previous cesarean sections was the main indication for cesarean section in the investigated service.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations